Evaluation of Three-Dimensional Cultured HepG2 Cells in a Nano Culture Plate System: an In Vitro Human Model of Acetaminophen Hepatotoxicity - Kohei Aritomi; Yoichi Ishitsuka; Yoshiro Tomishima; Daisuke Shimizu; Nazuki Abe; Tsuyoshi Shuto; Mitsuru Irikura; Hirofumi Kai; Tetsumi Irie (Elsevier, 2014)
Overdoses of acetaminophen (paracetamol, N-acetyl-p-aminophenol; APAP) cause severe liver injury, yet there is no common or high throughput in vitro human APAP model. This study examined the characteristics and usefulness of HepG2 cells grown in a nano culture plate (NCP) system, a three-dimensional culture method, as an in vitro human model for APAP-induced hepatotoxicity. The NCP-cultured HepG2 cells showed higher expression of mRNA and protein levels of cytochrome P450 2E1, which metabolizes APAP to a toxic metabolite, APAP-cysteine adduct formation, and higher sensitivity against APAP-induced cell injury compared with conventionally cultured cells. We demonstrated that treatment of APAP in NCP-cultured HepG2 cells shows key mechanistic features of APAP-induced hepatotoxicity, such as decreases in intracellular glutathione and mitochondrial membrane potential, activation of JNK, and cellular injury; and pharmacological agents, such as Cyclosporine A (a mitochondrial permeability transition inhibitor) and SP600125 (a JNK inhibitor), prevented cell injury induced by APAP exposure. In addition, the antidote of APAP-induced hepatotoxicity, N-acetylcysteine, could attenuate cellular injury induced by APAP in NCP-cultured HepG2 cells. We suggest that cellular injury induced by APAP treatment using an NCP-HepG2 system is a useful human model to study mechanisms and screen drug candidates of APAP-induced hepatotoxicity. [Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.13135FP] Keywords:: acetaminophen, liver injury, HepG2 cell, three-dimensional culture, human model